ПРОБЛЕМИ ЗМІСТУ КОМПЕТЕНТНОСТІ ВИКЛАДАЧА ПЕРЕКЛАДУ - Ольховська, Алла (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Статтю присвячено аналізу існуючих підходів до змісту компетентності викладача перекладу. Розглянуто погляди на визначення зазначеного поняття. Надано його компонентний склад та розкрито суть окремих компонентів. Акцентується увага на необхідності спеціального формування компетентності викладача перекладу. Робиться висновок про те, що її складові потребують детальнішого вивчення з метою їх подальшого включення до процесу навчання майбутніх фахівців з викладання перекладу, що сприятиме оптимізації такого процесу. Статья посвящена анализу существующих подходов к содержанию компетентности преподавателя перевода. Рассмотрены взгляды на определение упомянутого понятия. Приведен его компонентный состав и раскрыта суть отдельных компонентов. Акцентируется внимание на необходимости специального формирования компетентности преподавателя перевода. Сделан вывод о том, что её составляющие нуждаются в более детальном изучении с целью их дальнейшего включения в процесс обучения будущих специалистов по преподаванию перевода, что будет способствовать оптимизации такого процесса. The article is devoted to the analysis of the existing approaches to the content of translator trainer competence. It outlines points of view on the definition of this notion, provides its componential composition and reveals the content of its separate components. In particular, the model of the translator trainer competence developed within the framework of the European Master’s in Translation includes five components: field competence, interpersonal competence, organizational competence, instructional competence, assessment competence. It is stressed that translator trainers have to receive special training aimed at the developing of the competence mentioned. The conclusion is drawn that the notion of translator trainer competence needs further research in order to incorporate its components into the process of teaching the would-be translator trainers which in its turn will contribute to the optimization of this process.